Pałuba w sieci porównań - Panek, Sylwia (Przestrzenie Teorii, 2017)
This is a review of Marcin Jauksz’s book Critique of 19th-century intellect. Sources and contexts in Karol Irzykowski's “Pałuba”; Universitas, Kraków 2015. The author contrasts Jauksz’s conclusions with those formulated years earlier by Jerzy Franczak when analysing Irzykowski’s novel in his book The quest for reality. The world view of Polish modernist prose (Poszukiwanie realności. Światopogląd polskiej prozy modernistycznej) (Universitas, Kraków 2007)